Promoter methylation and increased expression of PD-L1 in patients with active tuberculosis - Tseng, Yen-Han; Pan, Sheng-Wei; Huang, Jhong-Ru; Lee, Chang-Ching; Hung, Jung-Jyh; Hsu, Po-Kuei; Chen, Nien-Jung; Su, Wei-Juin; Chen, Yuh-Min; Feng, Jia-Yih (Microbial cell, 2024)
The PD-1/PD-L1 pathway plays a pivotal role in T cell activity and is involved in the pathophysiology of Mycobacterium tuberculosis (MTB) infection. DNA methylation is a mechanism that modulates PD-L1 expression in cancer cells. However, its effect on PD-L1 expression in macrophages after MTB infection remains unknown. We prospectively enrolled patients with active tuberculosis (TB) and non-TB subjects. The expression of PD-L1 and methylation-related genes in peripheral blood mononuclear cells (PBMCs) were investigated and their correlation with disease severity and treatment outcomes were examined. PD-L1 promoter methylation status was evaluated using bisulfite sequencing. Immunohistochemistry (IHC) and immunofluorescence (IF) staining were used to visualize PD-L1- and TET-1-expressing cells in lung tissues from patients with TB and in macrophage cell lines with MTB-related stimulation. In total, 80 patients with active TB and 40 non-TB subjects were enrolled in the analysis. Patients with active TB had significantly higher expression of PD-L1 , DNMT3b , TET1 , TET2 , and lower expression of DNMT1 , compared to that in the non-TB subjects. The expression of PD-L1 and TET-1 was significantly associated with 1-month smear and culture non-conversion. IHC and IF staining demonstrated the co-localization of PD-L1- and TET-1-expressing macrophages in patients with pulmonary TB and in human macrophage cell lines after MTB-related stimulation. DNMT inhibition and TET-1 knockdown in human macrophages increased and decreased PD-L1 expression, respectively. Overall, PD-L1 expression is increased in patients with active TB and is correlated with treatment outcomes. DNA methylation is involved in modulating PD-L1 expression in human macrophages.